DEVELOPMENT OF AUGMENTED REALITY BASED SNAKES AND LADDERS GAME TO ENHANCE SOCIAL STUDIES LEARNING MOTIVATION AND ENVIRONMENTAL AWARENESS - Ardania; Prastiyono, Hendri; Segara, Nuansa Bayu; Hasanah, Nurul; Dizon, Carmela S. (Jurnal Pendidikan Ilmu Sosial, 2025)
This study aims to develop a snake and ladder game media based on Augmented Reality that is feasible and effective in increasing the motivation to learn social studies and environmental awareness. This development research uses the Borg and Gall model modified into 8 stages, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision (6) product trial (7) product revision (8) usage trial. The research design uses a quasi-experimental design with nonequivalent controlgroup design. This study involved media experts, material experts, social studies teachers, and eighth-grade students of SMP Labschool UNESA 2. Data were collected through interviews, observations, questionnaires, and tests. The results of the study showed that the snake and ladder game media based on augmented reality was declared "very feasible". The N-gain test results showed that social studies learning motivation obtained 0.61 and environmental awareness of 0.56, in the moderate category. These results indicate that the snakes and ladders game media based on augmented reality is quite effective in increasing social studies learning motivation and environmental awareness. In addition, the results of the independent sample t-test showed a significance value of 0.00 < 0.05, there was a significant difference between the experimental and control classes, which had a significant effect on social studies learning motivation and environmental awareness. Therefore, the snakes and ladders game media based on augmented reality can be used by teachers as an alternative interactive and interesting social studies learning media to encourage active student involvement.